Implementasi Pendidikan Inklusif bagi Anak Berkebutuhan Khusus (ABK) di SD Swasta Srikandi Kota Lhokseumawe - Ani Nasution; Ferizaldi Ferizaldi; Aflia Rizki; Asrul Fahmi; Lisa Iryani (Jurnal Ilmu Sosial dan Humaniora, 2026)
ABSTRACT This study aims to analyze the implementation of inclusive education policy for children with special needs (CSN) at SD Swasta Srikandi, Lhokseumawe City, the school with the highest number of CSN in the city, while identifying the barriers affecting its implementation. A descriptive qualitative approach was employed, with informants selected through purposive and accidental sampling, comprising the school principal, teachers, an Education Office official, and parents. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model, with validity established through source and method triangulation. Findings, analyzed through Van Meter and Van Horn's policy implementation theory, reveal an uneven pattern across indicators: policy standards and objectives are clearly defined, yet human, financial, and infrastructural resources remain severely limited marked by the absence of Special Assistant Teachers and inadequate accessibility facilities while implementers' disposition remains consistently positive, functioning as a temporary buffer against these resource deficits. These findings confirm that successful policy implementation depends on the simultaneous interaction among indicators rather than clarity of objectives alone, with practical implications underscoring the urgency of providing Special Assistant Teachers, sustained training, and needs-based resource allocation. Further research is recommended to broaden the scope of locations and adopt mixed-methods approaches.